The resilience of public sector management: a systematic literature review - Zahari, Afzal Izzaz; Azhar, Zubir; Said, Jamaliah; Muhamad, Nurisyal (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
Common ground issues remain unresolved in public sector management worldwide. Limited systems and a lack of resources require governments to evaluate their approaches when managing public sector organisations. Improving organisational resilience is deemed crucial to prevent harmful effects on the government, such as mismanagement and inefficiency in delivering public services. Thus, this systematic literature review sought to intensify the understanding of the link between management and organisational resilience in the public sector context. This study reviewed past public sector management theories, concepts, and models based on 399 accessed works of the published literature. In order to achieve an effective management approach, common themes were identified to obtain in-depth insights on definitions, applications, and challenges in public sector management, including digitalisation and governance areas. The findings suggested that the technological themes were crucial in achieving resilient public sector management. Recent findings of practice applications provide relevance to current public sector management issues. An opportunity exists for public sector organisations to improve their overall performance and achievements through efficient public sector management. Developing clear goals and designing strategic technological implementation are potential areas that must be explored in the public management literature.